Hematological Biomarkers Associated with Stroke Types: A Clinical Cross-Sectional Analysis - Beatriz Macacari; Beatriz Roberta da Silva; Maria Eduarda Ferreira Pereira; Lívia Maria de Jesus Pereira; Ana Beatriz Perez Bertochi; Gabriela Torres Pinheiro; Marcela Arietti; Ana Quevedo; Nailza Maestá; Cláudio Lera Orsatti (Journal of Vascular Diseases)
Background: Stroke is a major cause of morbidity and mortality worldwide, with distinct pathophysiological mechanisms between ischemic stroke (IS) and hemorrhagic stroke (HS). Hematological parameters, such as lymphocyte and erythrocyte count, have been implicated in stroke prognosis, but their predictive value remains uncertain. Objective: To evaluate the association between hematological biomarkers and stroke subtypes (ischemic stroke and hemorrhagic stroke), and transient ischemic attack. Methods: This cross-sectional study analyzed clinical, metabolic, and hematological parameters in patients with stroke. Logistic regression models, adjusted for age, gender, and ethnicity, were applied to assess the association between lymphocyte and erythrocyte counts and stroke subtypes. Results: Lymphopenia was significantly associated with higher odds of hemorrhagic stroke (HS) in both the TIA–HS (OR 1.15, 95% CI: 1.05–1.26, p = 0.004) and the IS–HS models (OR 1.11, 95% CI: 1.03–1.20, p = 0.009). Additionally, erythrocyte count was significantly associated with increased odds of conversion from IS to HS (OR 3.97, 95% CI: 1.45–10.89, p = 0.007). The lymphocyte-to-monocyte ratio (LMR) was significantly different between IS and HS (OR = 1.38, 95% CI: 1.07–1.78, p = 0.014), while no significant association was found between TIA and HS (p = 0.399). Conclusions: Hematological parameters varied among stroke subtypes, with lymphopenia associated with hemorrhagic stroke and erythrocyte count differing between IS and HS. While these findings may aid in stroke characterization, further studies are needed to confirm their clinical relevance.